THE RIGHT OF PEOPLES TO SELF-DETERMINATION IN THE POST-SOVIET COUNTRIES - Soloviova, Alina; Mamonov, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article is to study the essence of the right of peoples to self-determination on the example of some post-Soviet countries. The methodological basis of the study consists of methods of cognition (analysis, synthesis, induction, deduction, analogy, comparison), general scientific methods, formal-logical method of interpretation of law, etc. The components of the methodological base are objectivity and a combination of critical and rational, constructive approaches. Results: after the collapse of the Soviet Union, the Socialist Republics became independent sovereign states, but formally rather than practically. The military conflicts in South Ossetia, Abkhazia and the Transnistrian Moldavian Republic, as well as Russia's ongoing war against Ukraine, have shown that there is still a need to reassess the role and importance of international political institutions and mechanisms for implementing international law. Discussion: the principles of territorial integrity of the state and the right of nations to self-determination are essentially related to the term «sovereignty», its interpretation and implementation in public policy. The different correlation of these principles in the state-building of modern countries leads to the intensification of geopolitical processes, often disintegration, which can lead to the development of various interethnic conflicts. The right to self-determination can be exercised in the form of autonomy within existing state borders, in the form of the creation of a sovereign state or in the form of the withdrawal of a certain people from the state (secession or irredentism). Following purely theoretical constructions, the «peoples» of South Ossetia, Abkhazia, and the Transnistrian Moldavian Republic have exercised their inalienable right to self-determination, and the «peoples» of Georgia and Moldova have violated their inalienable rights. Russia's aggression against Ukraine has become a shining example of the abuse of irredentist sentiments in society to justify armed aggression. A comparative analysis of irredentist attitudes in the civil society of post-Soviet countries allows us to highlight the features of such trends, as well as their impact on foreign policy.